Linking Seasonal Reduction of Microbial Diversity to Increase in Winter Temperature of Waters of a Chilean Patagonia Fjord - Gutiérrez, Marcelo H.; Narváez, Diego; Daneri, Giovanni; Montero, Paulina; Pérez-Santos, Iván; Pantoja, Silvio (Frontiers in Marine Science, 2018)
Since microorganisms play a major role in the biogeochemistry of the ocean, understanding structure and dynamics of natural microbial communities is crucial in assessing the impact of environmental changes on marine ecosystems. In order to identify key environmental drivers of microbial community structure in Chilean Patagonian fjords, we analyzed composition of the prokaryotic community over an annual cycle at a single sampling site in Puyuhuapi Fjord. Distinctive communities represented mainly by Actinomycetales, Rhodobacteraceae, Cryomorphaceae, and Flavobacteriaceae were associated with Estuarine Fresh Waters, whereas Cenarchaeaceae and Oceanospirillales were representative of Modified Sub Antarctic Waters present in the fjord. Salinity and oxygen were first-order factors explaining segregation of microbial communities in these contrasting water masses. Positive correlations of members of Flavobacteriaceae, Alteromonadales, and Verrucomicrobiales with diatoms in subsurface waters and of Flavobacteriales (Cryomorphaceae and Flavobacteriaceae), Rhodobacteraceae, and Pelagibacteraceae with dinoflagellates in surface waters suggest that phytoplankton composition could define specific niches for microorganisms in Puyuhuapi fjord waters. A dramatic reduction of richness and individual abundances within Flavobacteriaceae, Rhodobacteraceae, and Cenarchaeaceae families was principally explained by seasonal increase of surface water temperature, with major reduction associated with changes in temperature during winter conditions. Taxa that are sensitive to increased temperature are key components of organic matter and element cycling, and we therefore suggest that potential decrease in diversity associated with rising of surface water temperature could impact current biogeochemical status of Patagonian fjord ecosystems.